Gregarious bamboo flowering opens a window of opportunity for regeneration in a temperate forest of Patagonia - Giordano, Carla Valeria (2009)
• Rare gregarious flowering of understorey bamboo species occurs in temperate and subtropical forests around the world, but the ecological consequences of this phenomenon for forest regeneration are not well understood. • Field experiments were conducted in an old-growth temperate forest in Patagonia, Argentina after a massive bamboo flowering event, to examine whether light quality and other changes in microhabitats could affect seed germination and growth of overstorey species. • Germination of southern beech (Nothofagus obliqua) was positively correlated with red:far red (R:FR) ratios in a range of microhabitats generated by the death of the understorey bamboo (Chusquea culeou). Experimental modification of understorey R:FR ratios to mimic alternative light environments reversed this germination response in plots with senescent understorey, but not in plots with live bamboo. Laboratory incubations demonstrated a significant interaction between R:FR ratios and thermal amplitude in promoting seed germination. Microhabitats also significantly affected the growth of emerged seedlings. • Microenvironmental changes generated by this flowering event appear to have opened a window of opportunity for germination and growth of overstorey species. We demonstrate that natural gradients in light quality associated with this ecological phenomenon are a major component affecting forest regeneration in this ecosystem.